PENYULUHAN ANTI NARKOBA DI SEKOLAH: MEMBANGUN GENERASI BEBAS NARKOBA SEJAK DINI - Bukhari, Bukhari; Setiawan, Setiawan; Taufiq, Taufiq; Hatta, M.; Zulfikar, Zulfikar; Anwar, Anwar (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2024)
Anti-drug counseling in schools is a strategic step in preventing drug abuse among teenagers. This activity aims to increase students' awareness of the dangers of drugs, build anti-drug attitudes, and develop social skills to deal with environmental pressure. Evaluation showed a significant increase in knowledge and changes in students' attitudes towards drug use. The implementation of methods such as presentations, discussions, simulations, and role plays proved effective in conveying the anti-drug message. Active support from the school and parents strengthened the impact of the counseling. The development of additional materials such as brochures and posters also expanded the reach of information. The results of this activity emphasize the importance of program sustainability and collaboration with various parties to shape a drug-free young generation. With a holistic approach, this activity contributes to efforts to create a safe and healthy school environment.